Degradation of β-Actin mRNA and 18S rRNA in mouse spleen cells after death - Zhiyuan An; Feng Li; Dong Zhao (Wolters Kluwer Medknow Publications, 2019)
We observed degradation of β-actin mRNA and 18S rRNA in mouse spleen cells under constant temperature conditions in the different temperature group during postmortem intervals (PMIs) of 0-72 h. Thirty-nine mice were sacrificed by cervical dislocation and kept at constant temperatures of 10°C, 15°C, 20°C, 25°C, and 30°C. From 0 to 72 h after death, total RNA in spleen cells was extracted every 6 h. The cycle threshold (Ct) values of β-actin mRNA and 18S rRNA were obtained by real-time-quantitative polymerase chain reaction. The results showed that, under the conditions of different and constant temperatures after mouse death at 72 h, the Ct values of β-actin and 18S, Ct ratios of β-actin to 18S, and relative ratios of β-actin to 18S were significantly correlated with PMI. In addition, the relative degradation rates of β-actin and 18S appeared to change from fast to slow with the increase of temperature. By interpolation and fitting analysis of the data, we obtained a ternary quintic equation of the relationship between the change in the relative ratios and PMI, which can be used to infer PMI within a certain temperature range (10°C-30°C).